Penataan Kelembagaan, Perubahan Paradigma Dan Pilihan Kebijakan Sebagai Langkah Strategis Menanggulangi Kemiskinan: Perspektif Administrasi Publik - Hutahaean, Marlan (Magister Administrasi Publik (MAP) FISIPOL Universitas Gadjah Mada, 2006)
The objective of this paper is to describe how the three strategies, institutional upgrading, paradigm change, and poluy choice, can be applied to alleviate poverty. A theoretical analysis is based on secondary data, result of the previous research and the outcome of policy implementation which are related in alleviating poverty in Indonesia. Based on this theoretical analysis, it is found that poverty is caused by institutional barrier, mistakes in selecting a development paradigm, and mistakes inseleselectingapolig